The Effect of Andaliman Fruit Extract (Zanthoxylum acanthopodium DC) on α-Synuclein Levels in Rotenon-Induced Wistar Rats - Citra Puan Maulidza; Binarwan Halim; Linda Chiuman; Atika Rimalda Nasution; Yohani Theresia (Jurnal Penelitian Pendidikan IPA, 2025)
Parkinson's disease is a neurodegenerative disorder characterized by loss of dopamine and formation of α-synuclein aggregates in the substantia nigra pars compacta (SNpc). This study aims to evaluate α-synuclein levels in the plasma of rotenone-induced Wistar rats as a model of Parkinson's disease and the therapeutic effect of Andaliman fruit extract. The design of this study was experimental with 25 male Wistar rats divided into five groups, negative control group (K-, only given distilled water), positive control (K+, induced rotenone 3 mg/kgBB/day for two weeks), and three treatment groups (P1, P2, P3) induced rotenone and given Andaliman extract orally at a dose of 150 mg/kgBB, 300 mg/kgBB, and 450 mg/kgBB respectively for 14 days. Measurement of levels was performed using ELISA on day 14 after induction and day 28 after therapy. The results of one-way ANOVA analysis showed that Andaliman extract significantly reduced α-synuclein levels at all doses compared to the positive control (p=0.000). The decrease in α-synuclein levels indicates the potential of Andaliman fruit extract in reducing Parkinson's disease-related pathology in mouse models.